PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, BUDAYA ORGANISASI DAN KOMPETENSI KERJA GURU ASN DAN NON ASN TERHADAP KOMITMEN KINERJA GURU UPT SDN 016505 - Anggeraini, Faulia; Tamba, Dang Panagaman (Smart Education, 2025)
Abstract: One of the standards that must be met in the implementation of education is the competency standard of educators and education personnel. According to Law Number 14 of 2005 concerning Teachers and Lecturers, Article 1 paragraph 1 states that